First Results from the 2dF QSO redshift survey - Boyle, B; Croom, S; Smith, R; Shanks, T; Outram, P; Hoyle, F; Miller, L; Loaring, N (2001)
We present some initial results from the 2dF QSO redshift survey. The aim of the survey is to produce an optically-selected catalogue of 25000 QSOs over the redshift range 0